Pelaksanaan Fungsi Audit Intern di Organisasi Nirlaba (Studi Kasus pada GMIM Jemaat Kristus Manado) - Maase, Alfian (Universitas Sam Ratulangi, 2014)
Christ Church GMIM Manado as a non-profit organization has had internal audit called BPPJ appropriate stewardship book GMIM Church of Christ Manado. BPPJ charge of fostering, or give direction (advices), ensure that there are adequate internal controls in the management of the treasury and fixed asset / inventory and inspection and monitoring to assess whether financial reporting and the asset is transparent and accountable in order to prevent fraud (crime) which can break up the unity of the church. Phenomena occurring in the church today is the emergence of divisions and mistrust due to the financial management of the perceived lack of transparency and accountability, so to sue each other in court and even in the church who have had BPPJ not necessarily be separated from the problem. This is due to the discharge of its functions BPPJ still face many struggles or obstacles that cause the performance of the functions of the internal audit BPPJ not been effective as it should be. This study aims to analyze how the internal audit function in the Church of Christ GMIM Manado. This study used a qualitative approach with a blend of ethnography and case studies. The conclusion of this study indicate that the performance of the functions of the Church of Christ GMIM BPPJ in Manado has not run due plagued with struggles that come both from outside and from within his own BPPJ, the integrity of the church and the conversion of those who make mistakes that become important points of the implementation of the functions BPPJ, and the commitment and surrender to the task of calling the main criterion for becoming a member BPPJ.